Analysis of Student Perceptions of Just-In-Time Teaching Pedagogy in PharmD Microbiology and Immunology Courses - Madiraju, Charitha; Tellez-Corrales, Eglis; Hua, Henry; Stec, Jozef; Nauli, Andromeda M.; Brown, Deborah M. (Frontiers in Immunology, 2020)
Just-In-Time Teaching (JiTT) active learning pedagogy is utilized by various disciplines, but its value in a professional pharmacy curriculum has not yet been demonstrated. The purpose of our research study is to implement and evaluate JiTT in a Doctor of Pharmacy (PharmD) program. The impetus in implementing JiTT into a PharmD curriculum was to provide students with an out-of-classroom learning opportunity to enhance knowledge-based skills. The current study summarizes the implementation of JiTT in four distinct instances: two iterations of the required courses “Integrated Microbiology and Virology” (Fall 2016 and Fall 2017) and “Integrated Immunology” (Winter 2016-2017 and Winter 2017-2018). JiTT included knowledge-based questions in multiple-choice format, integrated case studies, and student responses prior to the actual lecture session. After the conclusion of each course, students were asked to provide feedback on the utilization of JiTT by way of an anonymous survey. Following the Fall 2016 iteration of the Microbiology & Virology course, students found the integrated case studies to be beneficial (mean = 3.27 out of a maximum of 4, SD = 0.62), and their overall endorsement of JiTT was high (mean = 3.61 out of 4, SD = 0.50). For the other three courses included in this study, the primary dependent variable was the student’s average rating of JiTT, rated on a five-point scale. Aggregating the scores from the Fall 2017 iteration of the Integrated Microbiology & Virology course and both instances of the Immunology course, students rated JiTT very favorably (mean = 4.17 out of a maximum of 5, SD = 0.77). Students’ performances in JiTT-based courses were compared against non-JiTT-based courses. Analysis of assessment data for student’s performance on knowledge-based questions showed JiTT was helpful for student learning and JiTT-based courses had more consistent exam scores compared to non-JiTT-based courses. The current results are a promising initial step in validating the usefulness of JiTT in a pharmacy program and lays the foundation for future studies aimed at a direct comparison between a traditional lecture style and JiTT pedagogy implemented into PharmD curricula.